1996
DOI: 10.1073/pnas.93.24.14065
|View full text |Cite
|
Sign up to set email alerts
|

Brain monoamine oxidase A inhibition in cigarette smokers

Abstract: Several studies have documented a strong association between smoking and depression. Because cigarette smoke has been reported to inhibit monoamine oxidase (MAO) A in vitro and in animals and because MAO A inhibitors are effective antidepressants, we tested the hypothesis that MAO A would be reduced in the brain of cigarette smokers. We compared brain MAO A in 15 nonsmokers and 16 current smokers with [ 11 C]clorgyline and positron emission tomography (PET). Four of the nonsmokers were also treated with the an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

12
219
3
3

Year Published

2001
2001
2014
2014

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 388 publications
(240 citation statements)
references
References 36 publications
(41 reference statements)
12
219
3
3
Order By: Relevance
“…When compared to former smokers and non-smokers, average reductions for current smokers are 30% and 40% for MAO A and B (Fowler et al, 2003a). These reductions are the result of chronic smoking behavior rather than a single administration of intravenous nicotine (Fowler et al, 1998a) or smoking a single cigarette (Fowler et al, 1999, and are less than those seen with antidepressant MAO inhibitors (Fowler et al, 1994;Fowler et al, 1996b). Additionally, a human post-mortem study of chronic smokers demonstrated a modest reduction in MAO A binding that did not reach statistical significance (Klimek et al, 2001).…”
Section: Monoamine Oxidase Function In Smokersmentioning
confidence: 97%
See 1 more Smart Citation
“…When compared to former smokers and non-smokers, average reductions for current smokers are 30% and 40% for MAO A and B (Fowler et al, 2003a). These reductions are the result of chronic smoking behavior rather than a single administration of intravenous nicotine (Fowler et al, 1998a) or smoking a single cigarette (Fowler et al, 1999, and are less than those seen with antidepressant MAO inhibitors (Fowler et al, 1994;Fowler et al, 1996b). Additionally, a human post-mortem study of chronic smokers demonstrated a modest reduction in MAO A binding that did not reach statistical significance (Klimek et al, 2001).…”
Section: Monoamine Oxidase Function In Smokersmentioning
confidence: 97%
“…Fowler and colleagues have performed a series of elegant studies demonstrating decreases in monoamine oxidase (MAO) A and B activity in cigarette smokers using the PET tracers [ 11 C] clorgyline (Fowler et al, 1996b) and ([ 11 C]L-deprenyl-D2) (Fowler et al, 1996a(Fowler et al, , 1998b, respectively. When compared to former smokers and non-smokers, average reductions for current smokers are 30% and 40% for MAO A and B (Fowler et al, 2003a).…”
Section: Monoamine Oxidase Function In Smokersmentioning
confidence: 99%
“…Stress-induced monoamine surges could be particularly damaging during fetal and childhood development. Thus, the determination of brain MAO A levels corresponding to high and low MAO A genotype at different developmental stages as well as their interaction with environmental factors such as smoking that can further inhibit brain MAO (Fowler et al 1996a(Fowler et al , 1996b pregnancy merits further investigation. Similarly, future studies to MAO evaluate the relationship between MAO A genotype and brain MAO A levels in diverse neuropsychiatric populations will allow determination of whether MAO A in the adult brain is differentially regulated in some neuropsychiatric diseases.…”
Section: Discussionmentioning
confidence: 99%
“…The relationship between MAO A genotype and brain MAO A activity has never been examined in vivo in healthy human subjects, however. The purpose of this study was to determine whether high and low MAO A genotypes correspond to high and low brain MAO A activity in normal healthy male subjects using the MAO A radiotracer, [ 11 C]-clorgyline and positron emission tomography (PET; Fowler et al 1996aFowler et al , 2001). …”
Section: Brain Mao Activity; Mao a Genotypementioning
confidence: 99%
“…Previous investigations of MAO-A activity in postmortem brain of AD were primarily negative, with no change reported in prefrontal cortex, and a decrease reported in the hypothalamus and caudate (7,8). Unfortunately, these studies were inconclusive because none of them addressed several recently discovered biases that influence MAO-A levels, such as cigarette smoking (9,10), exposure to current or past major depressive episodes (11)(12)(13), and impulsive-aggressive personality traits (14,15). The latter covary with MAO-A levels, likely because of a neurodevelopmental influence of inherited MAO-A levels (16).…”
mentioning
confidence: 93%